Letter from Georg Bredig to Max Bredig, June 11, 1938 - Bredig, Georg (1938)
In a letter to his son, Max Bredig (1902-1977), Georg Bredig (1868-1944) provides professional advice and conveys updates on family and friends in Germany. Georg mentions the worsening circumstances for German Jews in Germany under the Third Reich.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Badger, Walter L. (Walter Lucius), 1886-1958; University of Michigan; Jewish Holocaust (1939-1945)